(untitled) (Colombia Medica, 2012)
Introduction: The puerperium is a stage that produces changes and adaptations in women, couples and family. Effective coping, during this stage, depends on the relationship between the demands of stressful or difficult situations and the recourses that the puerperal individual has. Roy (2004), in her Middle Range Theory about the Coping and Adaptation Processing, defines Coping as the “behavioral and cognitive efforts that a person makes to meet the environment demands”. For the puerperal individual, the correct coping is necessary to maintain her physical and mental well being, especially against situations that can be stressful like breastfeeding and return to work. According to Lazarus and Folkman (1986), a resource for coping is to have someone who receives emotional support, informative and / or tangible. Objective: To review the issue of women coping and adaptation during the puerperium stage and the strategies that enhance this adaptation. Methods: Search and selection of database articles: Cochrane, Medline, Ovid, ProQuest, Scielo, and Blackwell Synergy. Other sources: unpublished documents by Roy, published books on Roy´s Model, Websites from of international health organizations. Results: The need to recognize the puerperium as a stage that requires comprehensive care is evident, where nurses must be protagonist with the care offered to women and their families, considering the specific demands of this situation and recourses that promote effective coping and the family, education and health services.